Products attributes as attraction and as pull factor towards sustaining visitation to Putrajaya Botanical Garden - Yahaya, Asmah; Mohd, Abdullah (Universiti Putra Malaysia Press, 2013)
Park visitation is a popular recreational activity among urban residents. The decision to visit a park is related to the park’s attraction as the pull factor. The attractions include park’s products such as its facilities, services and programmes provided by the management. In many situations, lack of attractive products or recreational opportunities contributes to the decline in its visitation. Since year 2005, Putrajaya Botanical Garden has faced a similar situation, whereby its low visitation could be associated to unexciting product features offered by the park’s management. In this study, an evaluation was carried out on the products’ performance in attracting people to visit the park. Hence, 18 park attributes were chosen as attractions or pull factors to determine their relationships with socio-demographic background of visitors and their visitation attributes. Income and education attainment were identified as the significant reasons of visitation to Putrajaya Botanical Garden. Among the most important findings is the “park tranquil setting”, which is considered to be the park’s biggest attraction, among other attributes. Based on the factor analysis, three key factors were identified and labelled as “facilities and park settings”, “services and key visitors’ attractions” and “programmes and activities”. Meanwhile, “facilities and park setting” also showed the strongest positive relationships to the visitors’ extent of visitation. The study revealed the attractiveness of the park’s products would have the influence on people’s decision to visit it. These findings therefore contribute to the important idea to the current understanding of pull factors that influence park visitation to Putrajaya Botanical Garden as a thematic nature park.